Evaluation of Lipid Profile and Inflammatory Parameters in Female Diabetes Type 2 Induced Rabbits Treated with Glimepride, Bromocriptine and Fluoxtein - Abbas, Areej Basil; Abbas, Duraid A. (The Iraqi Journal of Veterinary Medicine, 2019)
This study was performed to evaluate the improvement in serum lipid profile and inflammatory parameters in female diabetic rabbits after two-month treatment with glimepride, bromocriptine, and fluoxtein in order to decrease the cardiovascular disease risk related to type 2 diabetes mellitus. Twenty-five local female rabbits were divided equally into five groups; four groups were diabetes type 2 induced by alloxan 120 mg/kg and nicotinamide 50 mg/kg, and the fifth group was control negative (Cv-). The animals were allocated to different treatment regimens, dosed orally on a daily basis for two months, as follows: T1 (glimepride 0.11 mg/kg),T2 (glimepride 0.11+bromocriptine 0.04 mg/kg),T3 (glimepride 0.11+fluoxtein 0.29 mg/kg), control positive group(Cve+) diabetic without treatment, and the fifth group was a control negative group (Cve-) dosed with distall water. Lipid profile, interleukin-6, and C-reactive protein were determined after diabetes induction and at the end of the experiment. IL-6 was significantly reduced in T2, while C-Reactive Protein was not significantly reduced. All treated groups showed nearly similar total cholesterol levels, demonstrating the higher level of high density lipoprotein-C level . At the same time, all treated groups showed a non-significant decrease in low density lippoprotein-C, and T2 showed superiority in reducing very low density lipoprotein-C and triglyceride levels over all other diabetic groups. In conclusion, diabetes agonist (Bromocriptine)+glimepride demonstrated superiority over the combination therapy glimepride+flouxtein and glimepride as monotherapy in improving diabetes type 2 related cardiovascular complications.